KONSEP PEMBELAJARAN YANG INOVATIF DALAM MENANGANI PROBLEMATIKA PEMBELAJARAN - Rifkisyahputra Rifkisyahputra; Unik Hanifah Salsabila; Muhaimi Puthaen; Ammar Hilay; M. Rizki Handrajati (Sekolah Tinggi Pariwisata Mataram, 2021)
In the learning process at every level of education there must be problems faced by various sectors, both educators, students and even learning support such as learning facilities and others. Problems that occur always have causes that are hereditary so that significant reforms are needed. The existence of significant reforms must have factors that encourage reforms to run smoothly so as to achieve the desired goals, namely to educate life and to prosper the people as stated in the Act as the government's obligation to provide rights to the community. One of the factors to achieve the desired goals, by making innovative learning concepts, there are several learning concepts, including: (1) innovative learning using PowerPoint in Arabic, (2) innovative learning using a concept map (mind map), (3) ) innovative learning using contexts